STRENGTHENING THE ROLE OF DEVELOPMENT INSTITUTIONS IN THE BANKING PROJECT FINANCING - I. A. Ezangina; N. A. Storozhilov (Финансы: теория и практика)
Topic. Currently, the particular relevance gains questions associated with the expansion of the amount of funding of investment projects, which are characterized by a high level of social and infrastructural importance to the national economy. It will also provide sustainable economic growth and diversification of the economy in the long term. In this regard, it actualizes the importance of development institutions, whose activities are aimed at overcoming ‘market failures’, to encourage the private investment by banks, and infrastructure development with use of mechanisms of state-private partnership.Purpose. The purpose of this work is an attempt to reveal the key importance of institutions and instruments of project financing in the implementation of the strategy of industrial and innovative development of the modern state.Methodology. To conduct the study there were used general scientific methods and techniques: methods of scientific abstraction, analogy, analysis, synthesis and comparison, the system-structural approach to the analysis of the research subject.Results. In the proof of the formation of the market of project financing, it was described in the dynamics its status and structure. There were identified issues, risks, and directions of development of the domestic market for stimulation of interest of banking organizations. Along with the traditional services provided to the borrower under the project financing, the attention is focused on the development of the Russian banking practice of promising areas (syndicated loans, mezzanine and bridge financing).Conclusions. We state the necessity of actualization of the mechanism of state-private partnership, particularly the role of development institutions. It has been proved the perspectivity of activities carried out at present by Industry Development Fund and State Corporation “Vnesheconombank”, namely: run the system of ‘one window’, the formation of the state information system of industry, development of the model of regional development funds for industry, an organization of banking syndicated loans, improvement of database management, launching operation of the “Factory of project financing”. The totality of the identified events will provide a permanent modernization of the Russian industry, and, along with the development of the banking sector with unique technology and knowledge, liquid and profitable assets.